Maturity Level Analysis in Software Development Using Scrum Methodology: Xyz Startup Case Study - Naomi Panjaitan; Bob Hardian (Asian Journal of Social and Humanities, 2023)
Startup XYZ is a pioneer in the EWA (Earned Wage Access) application in Indonesia which has been around since 2020. The main vision of Startup XYZ is to build financial health for low and middle income workers in Asia. In achieving its vision and facing current competitors, Startup XYZ continues to innovate to meet market needs. XYZ startup uses the Scrum methodology in the application development process. It was found that there were several problems that occurred, namely the development process was not optimal, causing the release plan to be delayed. This problem is considered to affect the quality and performance of Startup XYZ. This study aims to measure the scrum maturity level of Startup XYZ so that recommendations can be made to improve the maturity level. Data were obtained from several sources such as interviews, observations, and questionnaires that adapted the Scrum Maturity Assessment. The results obtained are calculated using the KPA Rating based on the Agile Maturity Model. Recapitulating the calculation of the maturity level of the scrum methodology, it is known that XYZ startup is still at level 2 with the Largely Achieved category. After obtaining the level of maturity for each level, recommendations are made based on the results of observations, Scrum Guide 2020, Scrum Essentials and SBOK v3. It was found that there were 24 recommendations to improve the maturity level of Startup XYZ